Pengajaran adab & akhlak islam dalam membangunkan modal insan - ASMAWATI SUHID, (Universiti Kebangsaan Malaysia, 2007)
The development of human capital can bring progress and excellence to human civilization. Hence, human capital development apparently is the main agenda for many nations including Malaysia. It is acknowledged that education is the most important medium in realizing this agenda. The human capital developed, however, must have strong spiritual and moral values; and this can be achieved, through education, by integrating in the curriculum the physical, emotional, spiritual and intellectual development of individual pupils. For Muslim pupils in Malaysia, spiritual and moral values are taught through the subject of Islamic Education. However, this effort has to be implemented earnestly, and it needs full commitment from various parties. This paper will discuss the teaching of Islamic Adab and Akhlak (a component of Islamic Education) in enhancing human civilization. It will further examine issues and problems faced in transmitting the Islamic Adab and Akhlak component, and will put forward views as well as measures to overcome related issues and problems